PENINGKATAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DALAM PENELITIAN TINDAKAN KELAS KOTA PALU SULAWESI TENGAH - Ramang Ramang (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
Teachers are educators who have a fundamental duty to implement learning activities. The task of the teacher is not light because it should improve the quality of human resources based on specific competency standards and norms and values that apply are the teacher in charge of transferring knowledge and skills in accordance with the applicable curriculum, teacher serves to enhance the knowledge and skills of students that will become the who has extensive knowledge and high skills, teachers must be good at motivating their students so that students are willing to be happy to develop and expand the knowledge and skills provided in the classroom, so that teachers are required to have pedagogical competence, personal competence, social competence and professional competence. Mastery of these competencies as a key to success for the conduct classroom action research in order to seek, find and give a solution to the problem of Islamic religious education lessons